Cyanotoxin Degrading Lake Bacteria Significantly Alleviate Microcystin-LR Induced Hepatotoxicity in Both In Vitro and In Vivo Models (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Research